Revised and Republished Ordinances of The City of Joplin, Missouri 201, § 75 (1903) - (:unkn) unknown (My University, 1903)
Ordinances that prohibit carrying concealed weapons, bringing weapons to certain places, and firing weapons, Ch. 23, Art. 1, Ord. No. 2019, § 75: If any person shall, in the City of Joplin, carry concealed upon or about his person, any deadly or dangerous weapon or shall go into any church or place where people have assembled for religious worship, or into a schocl room or place where people are assembled for educational, literary or social purposes, or to any election precinct on any election day, or into any court room during the sitting of court, or into any other public assemblage of persons met for any lawful purpose other than for militia drill or meetings, called under the militia law of this State, having upon or about his person any kind of fire-arms, bowie knife, dirk, dagger, slung-shot, or other deadly weapon, or shall, in the presence of one or more persons exhibit any such weapon, in a rude, angry or threatening manner, or shall have or carry any such weapon upon or about his person when intoxicated or under the influence of intoxicating drinks, or shall directly or indirectly sell or deliver, loan or barter to any minor any such weapon without the consent of parent or guardian of said minor, any such person shall be deemed guilty of a misdemeanor, and upon conviction, shall be punished by a fine of not less than fifty dollars, nor to exceed two hundred dollars, or by imprisonment in the city prison not less than five days, nor more than six months, or by both such fine and imprisonment
Keywords: BRANDISHING; CARRY - CONCEALED; SENSITIVE PLACES; TRANSFER - MINORS